2013
DOI: 10.3109/19396368.2012.758790
|View full text |Cite
|
Sign up to set email alerts
|

Ion currents modulating oocyte maturation in animals

Abstract: Growing oocytes are arrested at the first prophase of meiosis which is morphologically identified by the presence of a large and vesicular nucleus, called the germinal vesicle. The dissolution of the germinal vesicle marks the resumption of meiosis during which the oocyte undergoes massive modifications up to the second meiotic block, which is removed at fertilization. The interval between the first and the second meiotic block is defined as maturation and the events occurring during this period are crucial fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0
4

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 115 publications
(102 reference statements)
1
18
0
4
Order By: Relevance
“…Data of the present study suggest that the extracellular Ca 2+ increased rate of abortive SEA during initial period (3 and 5 h) of in vitro culture, while all eggs underwent abortive SEA if cultured for 7 h either in Ca -induced abortive SEA. These data suggest that the L-type Ca 2+ channels are still operated in ovulated eggs [37] and nifedipine blocks L-type Ca 2+ channels and inhibits abortive SEA in rat eggs [29]. These data together with previous findings suggest that postovulatory aging induces abortive SEA probably by increasing cytosolic free Ca 2+ level.…”
Section: Discussionsupporting
confidence: 74%
“…Data of the present study suggest that the extracellular Ca 2+ increased rate of abortive SEA during initial period (3 and 5 h) of in vitro culture, while all eggs underwent abortive SEA if cultured for 7 h either in Ca -induced abortive SEA. These data suggest that the L-type Ca 2+ channels are still operated in ovulated eggs [37] and nifedipine blocks L-type Ca 2+ channels and inhibits abortive SEA in rat eggs [29]. These data together with previous findings suggest that postovulatory aging induces abortive SEA probably by increasing cytosolic free Ca 2+ level.…”
Section: Discussionsupporting
confidence: 74%
“…It has been shown that estrogen plays a key role in oocytes maturation in mammalian models by inducing a series of cellular signaling including inositol triphosphate (IP3) and ryanodine (Ry)-mediated intracellular free calcium concentration ([Ca 2+ ]i) [23][24][25][26] and calcium signaling [27]. The development of the ability of oocytes to release Ca 2+ in response to the fertilizing spermatozoa is an essential step during oocyte maturation [28].…”
Section: Discussionmentioning
confidence: 99%
“…En aquellos ovocitos listos para madurar, durante las primeras horas de la maduración ovocitaria, tras la unión de la hormona LH con sus receptores, presentes en las células murales de la granulosa (Mehlmann, 2005;Sirard et al, 2006;, las células del cúmulo juegan un papel fundamental (Merton et al, 2003), ya que es en las 12 primeras horas tras el pico de LH cuando se produce la disrupción de las uniones entre las células del cúmulo y el ovocito (Tosti, 2006), así como su expansión y modificación . De hecho, la reanudación de la meiosis podría estar inducida por la generación de señales que se transfieren al ovocito, por la pérdida de contacto entre el ovocito y el ambiente folicular o por ambas (Tosti, 2006).…”
Section: Desarrollo Folicularunclassified
“…De hecho, la reanudación de la meiosis podría estar inducida por la generación de señales que se transfieren al ovocito, por la pérdida de contacto entre el ovocito y el ambiente folicular o por ambas (Tosti, 2006).…”
Section: Desarrollo Folicularunclassified
See 1 more Smart Citation